Polityka energetyczna Polski do 2040 roku – przejaw realizmu czy wishful thinking? .......... 117 - Koczan, Marcin (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The article concerns plans for the development of the energy sector presented by the Polish government in the draft document Polish energy policy until 2040. The author focuses on several crucial closely related factors such as the share of coal in Poland’s energy balance, the possibility of its replacement by renewable energy sources and nuclear power and at the transition stage through natural gas. The author analyses the Government’s assumption regarding the development directions of the energy sector in Poland over the next two decades and assesses the chances of their effective implementation.